PENGARUH WAKTU PROSES DEEP CRYOGENIC TREATMENT TERHADAP STRUKTUR MIKRO, KEKERASAN, DAN KEAUSAN PADUAN Fe-Al-Mn-Mo - Fila Delfianto Maitano, Angelio; Ratna Kartikasari,; Rivan Muhfidin, (ReTII, 2022)
Fe-Al-Mn-Mo alloy is an alloy steel that includes stainless steel that is a candidate for replacing conventional stainless steel with Fe-Cr-Ni alloys. This study aims to study the effect of Deep Cryogenic Treatment (DCT) processing time on the microstructure, hardness, and wear of Fe-Al-Mn-Mo alloys. The material used in this research is Fe-Al-Mn-Mo alloy steel castings. The composition test is carried out to determine the content contained in the test material, then specimen preparation is carried out by cutting the material into specimens. The process carried out is DCT by immersion in liquid nitrogen at a temperature of -196ËšC with time variations of 1, 2, 3, 4, and 5 hours. Then it is returned to room temperature. The tests carried out are microstructure testing, hardness testing, and testing The chemical composition test shows that the Fe-Al-Mn-Mo alloy has the main elements, namely Fe by 76.52%, the main alloying elements Mn by 14.11%, Al by 10.62%, and Mo by 0.45% and Fe-Al-Mn-Mo alloys are high alloy steels. Microstructure testing shows that Fe-Al-Mn-Mo alloys have ferrite and austenite structures. The DCT process causes the ferrite structure to get bigger and bigger while the austenite structure gets smaller and smaller than the grains The austenite will spread more and more between the ferrite grains. The hardness test shows an insignificant increase in hardness. Wear testing shows a decrease in wear rate.